PENGARUH PENGGUNAAN APLIKASI KALENDER PINTAR (KALPIN) TERHADAP PENINGKATAN SELF EFFICACY PENDERITA HIPERTENSI DI DESA KALIANGKRIK - Nur Faizah, Kartika; Sarwono, Bambang; Ashar Nurahman, Novema; Giri Kriwoyo, Pramono (Jendela Inovasi Daerah, 2025)
Hypertension is one of the dangerous diseases, earning the nickname "The Silent Killer." Hypertension can be controlled with good self-management. Factors influencing hypertension self-management include age, gender, occupation, family support, level of knowledge, and self-efficacy. Self-efficacy refers to an individual's belief that determines the extent of their ability and motivation in managing hypertension. Kalpin (Smart Calendar) is an Android-based mobile application that provides essential features to support self-management for hypertension patients. This study aims to determine the extent of the impact of using the Smart Calendar (Kalpin) application on improving the self-efficacy of hypertension patients in Kaliangkrik Village. The research design applied a pre-experimental approach with a single group (one group pretest-posttest without control group). The sampling technique used was purposive sampling with non-probability sampling. The research instrument used was a questionnaire titled "Self-Efficacy for Managing Hypertension," with a sample size of 44 hypertension patients in Kaliangkrik Village. The hypothesis test results using paired t-test showed a p-value of <0.001 (p-value = <0.05), indicating that there is an effect of using the Smart Calendar (Kalpin) application on improving the self-efficacy of hypertension patients in Kaliangkrik Village. However, the calculation of the effect size using Cohen's d showed 0.01, indicating a very small effect. This means that while the use of the Smart Calendar (Kalpin) application does affect the self-efficacy improvement of hypertension patients in Kaliangkrik Village, the effect is very small. Therefore, the use of the Smart Calendar (Kalpin) application influences the improvement of self-efficacy in hypertension patients in Kaliangkrik Village, but the influence is very minimal.